COMPUTERIZED AND DYNAMIC ELECTROCARDIOGRAPHIC EVALUATION IN DOGS WITH ACUTE NORMOVOLEMIC ANEMIA - CHAMPION, T.; PEREIRA NETO, G. B.; PAULINO JUNIOR, D.; FRANCO, R. P.; PASCON, J. P. E.; CAMACHO, A. A. (Ars Veterinaria, 2011)
The cardiovascular response to acute normovolemic anemia is related to activation of compensatory mechanisms that can cause changes in the electrocardiogram. The electrocardiographic examination demonstrates the occurrence of arrhythmias and may suggest the presence of atrial and ventricular enlargement or myocardium hypoxia. The aim of this study is to describe cardiac rhythm, heart rate and ECG pattern in dogs undergoing acute normovolemic anemia. The dogs were submitted to computerized electrocardiography 15 minutes and 24 hours after induction of anemia and evaluated by Holter, with 24 hours of continuous electrocardiographic monitoring. Anemic dogs had no arrhythmias or premature ventricular and atrial complexes related to hypoxia and it were observed reductions in the incidence of sinus arrhythmia. Although there was no development of sinus tachycardia, there was a significant increase (P = 0.01) in heart rate (bpm) in both assessments made after installation of anemia (100.90 ± 23.1 to 132.50 ± 12.7 and 132.70 ± 23.9). The increased heart rate was linearly related to the fall in hematocrit (R2 = 0.27, P = 0.018). In addition, this study identified changes in the amplitude and duration of P wave and PR interval, without clinical significance because they were within the normal range for the specie. Therefore, dogs with acute normovolemic anemia and volemic reposition with Ringer's lactate solution and hydroxyethyl starch-based, with hematocrit of 14.37 ± 2.99%, did not develop significantly arrhythmias, extrasystoles or electrocardiographic patterns consistent with myocardial hypoxia and the electrocardiographic changes found may be related compensatory mechanisms activated.